Nilai-nilai Christus Vivit bagi Kaum Muda di Era Digital - Adrian Yanuar P; Teresia Noiman Derung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The digital era has brought significant transformation in the lives of young people, creating both opportunities and challenges for the expression of spiritual values. This study aims to identify and analyze the implementation of the values of Christus Vivit as a spiritual guide for young people in facing the challenges of the digital age. Through a literature review method, this research examines various sources related to Christus Vivit and its relevance to contemporary digital phenomena. The research findings identify four key values of Christus Vivit that are relevant for young people in the digital era: a personal relationship with the living Christ as a spiritual foundation in facing the influx of digital information; freedom and responsibility in the digital realm to filter information and adopt a critical attitude; solidarity and authentic community as an alternative to shallow virtual connections; and discernment and digital wisdom. These findings imply the need for the development of a spiritual mentoring model that integrates Christus Vivit values with digital competencies, so that young people can become wise users of technology while authentically practicing the Christian faith amid the complexities of the digital world.